The Culture of “Hijabers” Top Class in Social Media: Counter Hegemony or Next Hegemony? (Netnographic Study on the Instagram Accounts of Dian Pelangi and Dato' Seri Vida) - Rahman, Khairul Arief (Universitas Islam Balitar, 2023)
This article will discuss how Muslim women currently support their Islamic views through clothing that has been constructed in such a way. One of them is the phenomenon of